THE EFFECTIVENESS OF USING AUTHENTIC TEXTS IN THE TEACHING READING COMPREHENSION - Islam, Syaiful; Santoso, Edi (ETERNAL (English, Teaching, Learning, and Research Journal), 2018)
It was conducted to investigate whether the use of authentic texts in the teaching of reading comprehension is effective. The design of the study was quasi-experimental with non-randomized pretest-posttest control group. The samples of this study were the eight grade of SMP Negeri 1 Lawang – Malang in the 2017/2018 academic year. The sampling technique applied was simple random sampling which was taken by using lottery. The result of the lottery showed that class VIII-I was chosen as the experimental group and class VIII-G as the control group. In collecting data, pretest – posttest used was in the form of multiple choice tests which covered the subject matter of reading comprehension. The pretest means of both groups were analyzed statistically by using Lavene’s. Lavene’s test revealed the significant value is .553 that is higher than .05. This result indicates that the difference between variances is not significant. This indicates that the subjects of experimental and control groups are not significantly different before the experiment in their pretest scores of reading comprehension test. Therefore, an independent t-test was used to analyze the posttest means. The result of research findings, it can be concluded that using authentic texts in teaching reading comprehension proved to be effective in increasing the students’ reading comprehension achievement. Thus, it is suggested that English teacher to utilize authentic texts in teaching reading comprehension.